Meriwether Smith papers, 1779-1792. - Smith, Meriwether, 1730-1790.
ALS (1779 February 21) written by Smith to John Page concerning the scarcity of provisions, depreciation of currency, potential of Virginia as a market for eastern states, and other economic and political consequences of the Revolution; letter (1779 May 17) written to Thomas Jefferson, governor of Virginia, and signed by Smith and Richard Henry Lee relating to acquisition of land from Delaware Indians; and photocopy of a financial agreement (1792 January 20) between Smith and John Beale.
In part, negative photocopy.
Delegate to U.S. Continental Congress and U.S. representative from Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beale, John, -- active 1792.; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Page, John, -- 1744-1808 -- Correspondence; Delaware Indians -- Land tenure; United States -- History -- Revolution, 1775-1783 -- Economic aspects; United States -- History -- Revolution, 1775-1783 -- Supplies and stores; United States -- Politics and government -- 1775-1783.; Virginia -- History -- Revolution, 1775-1783 -- Economic aspects; Delegates, U.S. Continental Congress -- Virginia; Representatives, U.S. -- Virginia